Not so different? Comparison of risk profile of gay men who acquired HIV while travelling with those who acquired HIV in Australia. (28th December 2017) - Brown, Graham; Prestage, Garrett; Down, Ian; Ellard, Jeanne; Triffitt, Kathy
Abstract: Issue addressed: Many countries now identify HIV and international mobility as a priority issue within a global and shared epidemic, including Australia. To support health promotion in this complex area, we investigated recent HIV infections that occurred among Australian gay men while travelling and compared to HIV infections that occurred in Australia. Methods: 446 gay men recently diagnosed with HIV completed an on‐line survey regarding the high risk event (HRE) where they believed that they acquired HIV. Those who acquired HIV while in their usual place of residence (308 men), those who were travelling within Australia (59 men), and those who were travelling overseas (79 men) were compared. Results: Those who acquired HIV while overseas had very similar risk profiles, sexual behaviour, and made similar assumptions about their partners and their own HIV status, as those who acquired HIV in Australia. Only HIV status disclosure at the HRE differed across locations ( P = .030). Three quarters (74.7%) of the men who acquired HIV while overseas were not diagnosed until they returned to Australia. Conclusions: Our findings challenge the idea that there are necessarily differences in behaviour and assumptions for HIV transmission in Australia and overseas. However, the men travelling may be in communities where HIV status is less commonly disclosed, and where HIV prevalence is higher. So what?: A deeper understanding of contextual factors may be required for HIV prevention and health promotion strategies targeting gay men travelling to locations with different cultural, HIV prevalence, and HIV testing considerations. This would also identify opportunities for new tools such as Pre‐Exposure Prophylaxis and self‐testing.